Rescuing masculinity: giving gender in the wake of China's marriage squeeze - Driessen, M; Sier, W (SAGE Publications, 2021)
China’s marriage squeeze poses a profound challenge to the construction of masculinity in rural regions, where marriage continues to play an important role in the production of gender identities, marking manhood and its virtues. What are the consequences when men fail to marry and to assert respected male seniority? We show that in the context of China’s imbalanced sex ratio, family members attempt to rescue or restore the dignity of their sons and brothers by “giving gender,” gestures of care that are aimed to bolster gender authenticity and thereby strengthen a young man’s marriage prospects. By discussing both the intergenerational and intragenerational dynamics of gender collaboration within the family, we furthermore challenge existing studies that project gender antagonism in the wake of radical demographic change, while complicating the image of China’s rural bachelors as social outcasts.